Transmission scheduling for broadcasting with two energy‐harvesting switching transmitters. Issue 2 (1st June 2013) - Zhou, Fangfang; Chen, Hongbin; Zhao, Feng
Abstract : To minimise transmission completion time in energy‐harvesting rechargeable communication systems, various transmission scheduling schemes have been proposed. However, they did not consider the issue where a transmitter may fail before completing the transmission. To resolve this issue, transmission scheduling for broadcasting with energy‐harvesting switching transmitters is studied. The broadcasting communication system consists of two transmitters and two users. The transmitters harvest energy independently and work alternately. The transmission scheduling problem is formulated as minimising the transmission completion time, under the energy causality constraint, the data transmission constraint, and the transmitter switching constraint. Transmitter switching is addressed by proving that a transmitter should not stop transmission before switching to the other transmitter and the switching threshold should be zero. Then, an optimal transmission policy is proposed based on earlier works on rate region and the transmitter switching mechanism. The proposed optimal transmission policy can achieve a larger rate region than several kinds of suboptimal transmission policies.